From value to velocity: The role of hedonic shopping motives in fueling impulse buying - Erwin Erwin; Francesco Chandra; Gefael Triady; Fachrul Maulana; Ivan N. Faronal (Jurnal Manajemen dan Pemasaran Jasa, 2026)
Modern marketing strategies have shifted from functional product introductions toward stimulating affective consumer responses that trigger low-involvement purchasing. This study examines the influence of advertising value on impulsive buying behavior, specifically analyzing the mediating role of hedonic shopping motives. Utilizing a quantitative approach, survey data were collected from 205 residents in Makassar City, Indonesia. Data were analyzed using Structural Equation Modelling-Partial Least Squares (SEM-PLS) via SmartPLS software. The results confirm that all four hypotheses (H1–H4) are supported, demonstrating that advertising value significantly impacts both hedonic motives and impulsive buying. Notably, the findings reveal the presence of partial mediation, where the indirect effect of advertising value on impulsive buying channelled through hedonic shopping motives is statistically stronger than the direct effect. These results imply that while advertising value directly stimulates spontaneity, its efficacy is significantly amplified when it successfully invokes the consumer's emotional and experiential shopping desires. Consequently, businesses should prioritize marketing communications that leverage emotional triggers to optimize impulsive purchasing outcomes.